Quercetin's Dual Mode of Action to Counteract the Sp1-miR-27a Axis in Colorectal Cancer Cells - Emanuele Fosso; Manuela Leo; Livio Muccillo; Vittorio Maria Mandrone; Maria Chiara Di Meo; Annamaria Molinario; Ettore Varricchio; Lina Sabatino (MDPI AG, 2023)
Quercetin (Qc) inhibits cell proliferation and induces apoptosis in a variety of cancer cells. The molecular mechanism of action has not been fully elucidated; however, interplay with some miRNAs has been reported, specifically with miR-27a, an onco-miRNA overexpressed in several malignancies. Here, we show that Qc reduces cell viability and induces apoptosis in HCT116 and HT-29 colon cancer cells, by upregulating negative modulators of proliferation pathways such as Sprouty2, PTEN and SFRP1. These are targets of miR-27a whose high expression is reduced by Qc. Moreover, miR-23a, and miR-24-2, the two other components of the unique gene cluster, and the pri-miRNA transcript are reduced, evoking a transcriptional regulation of the entire cluster by Sp1. Mechanistically, we show that Qc is rapidly internalized and localizes in the nucleus, where it likely interacts with Sp1, inducing its proteasomal degradation. Sp1 is further repressed by ZBTB10, an Sp1 competitor for DNA binding that is an miR-27a target and whose levels increase following Qc. SP1 mRNA is also reduced, supporting the regulation of its own gene transcription. Finally, Sp1 knockdown elicits the impaired transcription of the entire cluster and the upregulation of the miR-27a targets, phenocopying the effects of Qc. Through this dual mode of action, Qc counteracts the protumoral Sp1-miR-27a axis, opening the way for novel therapies based on its association as neoadjuvant with known anticancer treatments.